Association of Thoracic Aorta Calcium Score With Exercise Blood Pressure Response and Clinical Outcomes in Elderly Individuals: Differential Impact of Aorta Calcification Compared With Coronary Artery Calcification. Issue 4 (22nd April 2016) - Cho, In‐Jeong; Chang, Hyuk‐Jae; Cho, Iksung; Heo, Ran; Lee, Sang‐Eun; Shim, Chi Young; Hong, Geu‐Ru; Chung, Namsik
Abstract : Background: The structure of the aorta is considered to influence exercise systolic blood pressure (SBP) response, which, in turn, might impact upon adverse outcomes. The current study sought to investigate the relationship of aortic calcification and exercise SBP with adverse outcomes among elderly individuals. Methods and Results: We retrospectively reviewed 702 elderly individuals (>65 years of age) without obstructive coronary artery disease (CAD; luminal stenosis <50%) who underwent coronary computed tomography (CT) and exercise treadmill testing. ΔSBPstage2 and ΔSBPpeak were defined as the difference in systolic blood pressure (SBP) between rest and stage 2 or peak exercise, respectively. Thoracic aortic calcium score (TACS) and coronary artery calcium score (CACS) were measured using CT scanning procedures. The primary endpoints were defined as all‐cause death, admission for heart failure, obstructive CAD requiring coronary intervention, and stroke. In multivariable models, ΔSBPstage2 and ΔSBPpeak were positively related withlog (TACS+1), even after adjusting for various clinical variables, baseline SBP, and CACS ( P <0.001). During a median follow‐up period of 65 months, there were 59 events (8.4%). In a multivariate Cox regression model, independent predictors for all events were age (hazard ratio [HR], 1.12; 95% CI, 1.05–1.19; P <0.001), dyslipidemia (HR, 1.96; 95% CI, 1.14–3.37; P =0.015), and the 4th quartile of TACS (HR, 1.24; 95% CI, 1.03–1.49; P =0.024). Among individual events, the 4th quartile of TACS was the only independent predictor for stroke (HR, 2.15; 95% CI, 1.09–5.13; P =0.044), whereas CACS ≥400 mm 3 was an independent predictor for obstructive CAD requiring intervention (HR, 7.04; 95% CI, 1.58–31.36; P =0.010). Conclusions: Aortic calcification was related to SBP response during exercise and was an independent predictor for outcomes, especially stroke, regardless of resting SBP or CACS.